Picture This: Preferences for Image Search - Bennett, Paul; Chickering, Max; Mityagin, Anton (Demo-paper in the Human Computation 2009 Workshop at KDD '09, 2009)
We demonstrate a system designed to elicit relative relevance judgments from users to rank images with respect to an image query. The system has been deployed and in use publicly for approximately one year. Furthermore, preference data collected from the users has been made available for research purposes. Further details regarding research on this system is available from Bennett et al. (WWW '09).